2015
DOI: 10.1097/ico.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-linking Combined With Simulation of Femtosecond Laser–Assisted Refractive Lens Extraction

Abstract: Adjunct CXL in this ex vivo simulation refractive lens extraction procedure seems to provide significant increase in corneal rigidity, up to +107%. These findings also support our previous reported work on laser in situ keratomileusis combined with CXL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The corneal samples had no statistically significant age, gender, or race difference; the operations were designed in a way they would reflect current clinical standards in our practice: the upper lamellar dissection in SMILE was created at 140 µm, and the femtosecond LASIK flap was created at 110 µm, exactly as in our clinical practice. To evaluate the effect on corneal biomechanical properties, we used biaxial stress–strain measurements, 27 , 28 which may be superior to corneal strip extensiometry used in earlier experiments considering the nonuniform topographic distribution of the corneal strength profile. 29 , 30 Thus, the orientation of the cornea specimens during the tensile measurements was intentionally random, to exactly address the fact that the in-plane biomechanical properties may naturally vary along different corneal meridians because of the known anisotropic differences of corneal collagen.…”
Section: Discussionmentioning
confidence: 99%
“…The corneal samples had no statistically significant age, gender, or race difference; the operations were designed in a way they would reflect current clinical standards in our practice: the upper lamellar dissection in SMILE was created at 140 µm, and the femtosecond LASIK flap was created at 110 µm, exactly as in our clinical practice. To evaluate the effect on corneal biomechanical properties, we used biaxial stress–strain measurements, 27 , 28 which may be superior to corneal strip extensiometry used in earlier experiments considering the nonuniform topographic distribution of the corneal strength profile. 29 , 30 Thus, the orientation of the cornea specimens during the tensile measurements was intentionally random, to exactly address the fact that the in-plane biomechanical properties may naturally vary along different corneal meridians because of the known anisotropic differences of corneal collagen.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the current work was unable to perform direct biomechanical measurements due to limited resources. Nevertheless, it had been shown that direct in vivo measurement of the corneal biomechanical property had low specificity and sensitivity [ 32 ]. The slight myopic shift demonstrated in our SMILE Xtra group could as well be due to an inadequate CXL effect to strengthen the cornea of our SMILE Xtra cases (where the preoperative corneas are thinner).…”
Section: Discussionmentioning
confidence: 99%
“…The slight myopic shift demonstrated in our SMILE Xtra group could as well be due to an inadequate CXL effect to strengthen the cornea of our SMILE Xtra cases (where the preoperative corneas are thinner). The strengthening effects of SMILE Xtra have been supported by an ex vivo study on human cornea by Kanellopoulos et al, which showed that combining cross-linking with refractive lenticule (5 mm diameter and 80 μ m thickness at 140 μ m depth) extraction resulted in significantly increased biomechanical properties compared with control non-cross-linked eyes [ 32 ]. We did not routinely check the endothelial cell count either, as it has already been shown that there was no significant change in the endothelial cell count before and after SMILE [ 33 ] or in SMILE Xtra [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biaxial stress–strain measurements were superior to corneal strip tensiometry. Previous studies have also shown that sclera exhibited a stress-hardening response when subjected to gradual tensile loads, demonstrating nonlinear characteristics. , The present study also indicated that the sclera is elastic and exhibits an obvious hysteresis phenomenon. This further indicates that the whole sclera exhibits major mechanical anisotropy.…”
Section: Discussionmentioning
confidence: 99%